Sampling of Shape Expressions with ShapEx - Basset, Nicolas; Dang, Thao; Gigler, Felix; Mateis, Cristinel; Nickovic, Dejan (2021 19th ACM-IEEE International Conference on Formal Methods and Models for System Design (MEMOCODE), 2021)
In this paper we present SHAPEx, a tool that generates random behaviors from shape expressions, a formal specification language for describing sophisticated temporal behaviors of CPS. The tool samples a random behavior in two steps: (1) it first explores the space of qualitative parameterized shapes and then (2) instantiates parameters by sampling a possibly non-linear constraint. We implement several sampling strategies in the tool that we present in the paper and demonstrate its applicability on two use scenarios.